2012
DOI: 10.1007/s00402-012-1552-1
|View full text |Cite
|
Sign up to set email alerts
|

Revision anterior cruciate ligament reconstruction: an update

Abstract: With the rising number of anterior cruciate ligament (ACL) reconstructions performed, revision ACL reconstruction is increasingly common nowadays. A broad variety of primary and revision ACL reconstruction techniques have been described in the literature. Recurrent instability after primary ACL surgery is often due to non-anatomical ACL graft reconstruction and altered biomechanics. Anatomical reconstruction must be the primary goal of this challenging revision procedure. Recently, revision ACL reconstruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 117 publications
2
34
0
2
Order By: Relevance
“…Causes of graft failure are multifactorial with the most important being trauma, technical error and failure of graft incorporation (12). It has not yet been determined which fixation method and what position of the drilling tunnels offers a lower rate of graft failure (12,13). Graft failure rate in our study was 12% and the result is comparable with previous papers, which reported graft failure of quadruple stranded STGR in 4% -15.3% (13,14).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Causes of graft failure are multifactorial with the most important being trauma, technical error and failure of graft incorporation (12). It has not yet been determined which fixation method and what position of the drilling tunnels offers a lower rate of graft failure (12,13). Graft failure rate in our study was 12% and the result is comparable with previous papers, which reported graft failure of quadruple stranded STGR in 4% -15.3% (13,14).…”
Section: Discussionsupporting
confidence: 83%
“…The most important finding of our study was the difference in IGSI between study groups. Causes of graft failure are multifactorial with the most important being trauma, technical error and failure of graft incorporation (12). It has not yet been determined which fixation method and what position of the drilling tunnels offers a lower rate of graft failure (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The remnant preserving technique, which provides more blood vessels and proprioceptive tissues, is demonstrated to result in increased ligamentization, ligament-bone integration and mechanical strength in animals [49][50][51]. By contrast, the delay or failure of vascularization is always associated with bad ligamentbone healing and insufficient ligament maturation, which may result in reconstruction failure as manifested by graft rupture and joint laxity [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…9 For the planning of surgical revision, prior tunnel placement is subcategorized into 3 types: (1) correct tunnel positioning with congruent previously placed and new tunnels, (2) cases of revision for incomplete and incorrect positioning, and (3) positioning with a bone bridge between the old and new tunnels. 10 …”
mentioning
confidence: 97%
“…9 For the planning of surgical revision, prior tunnel placement is subcategorized into 3 types: (1) correct tunnel positioning with congruent previously placed and new tunnels, (2) cases of revision for incomplete and incorrect positioning, and (3) positioning with a bone bridge between the old and new tunnels. 10 The surgical technique for ACL revision remains a matter of debate. If bone tunnels are not widened and are in the correct position, single-stage reconstruction can be performed.…”
mentioning
confidence: 99%